Gastric microbiota composition in patients with corpus atrophic gastritis. Issue 12 (December 2021) - Conti, Laura; Borro, Marina; Milani, Christian; Simmaco, Maurizio; Esposito, Gianluca; Canali, Giulia; Pilozzi, Emanuela; Ventura, Marco; Annibale, Bruno; Lahner, Edith
Abstract: Background: In corpus atrophic gastritis (CAG), hypochlorhydria makes plausible the overgrowth of intragastric bacteria, whose role in gastric carcinogenesis is under debate. Aims: To characterize the antrum/corpus composition of the gastric bacterial microbiota in CAG patients compared to controls without CAG. Methods: A cross-sectional monocentric study on consecutive patients with known histological diagnosis of CAG undergoing gastroscopy for gastric cancer surveillance and patients without CAG undergoing gastroscopy for dyspepsia or anemia (108 biopsies from 55 patients, median age 61.5). Genomic DNA from one antral and one corpus biopsy from each case ( n = 23) and control ( n = 32) was extracted. Gastric microbiota was assessed by sequencing hypervariable regions of the 16SrRNA gene. Results: Bacterial abundance and diversity were significantly lower in CAG cases than in controls ( p < 0.001). Firmicutes were more frequent in cases, Bacteroidetes and Fusobacteria in controls ( p < 0.0001). Streptococcaceae were more abundant in cases ( p < 0.0001), Prevotellaceae in controls ( p < 0.0001). The genus Streptococcus was positively correlated with severe OLGA/OLGIM stages linked to a higher risk of gastric cancer. Conclusion: Gastric bacterial microbiota in CAG showed a reduced abundance and complexity but was characterized by higher colonization of Firmicutes, in particular Streptococcus, increased in subjects with severe atrophy/metaplasia stages at higher risk of gastric cancer.